Intersectionality as an emerging discipline in the 21st Century Women Studies - Qudsia , Asra (South Asian Journal of Social Sciences and Humanities, 2020)
The Civil Rights Movement and Feminist Movement in the 1960’s America fought for their basic  rights and eventually were successful in achieving them. These two movements promised a new  beginning for African-American men and White American women, but ironically these movements  were relegating an equally important issue and that was of Black American women. Both the Civil  Right and Feminist activists did not fulfill their promise to help Black women of America to come  out of their century’s old bondage of multi-dimensional oppression. It was high time for black  women activists, writers and intellectuals to raise their voice against the injustice they faced in their  own homes where they confronted domestic violence in the hands of male family members and in  the homes of their white masters and landladies where these black women worked as maids or nannies. Black feminists argued that feminism which was in vogue at the middle of the 20th century  has always been Euro-centric in its approach; they didn’t see a promising future for themselves even  when Civil rights movement was successful. For them, it was male dominated movement, sexiest and misogynist in its approach. Also, feminism was not giving enough space to black women as it always carried white supremacy at its core. Black women were left out in protest and rallies which were organized by white middle class American women because of the racist attitude. Black women of America started their own campaign against the oppression they faced in the society  to make their voices heard and their identities recognized. In this paper, I have tried to present the  core issues of Intersectionality (study of multiple oppressions), its inclusive nature, its difference from traditional feminism and the major arguments of Intersectional theorists who have tried to use  Intersectionality as a new research paradigm in women studies.
Keywords: Intersectionality; African-American women studies; multi-dimensional oppression; Black Feminism